Dehydroepiandrosterone and Its CYP7B1 Metabolite 7α-Hydroxydehydroepiandrosterone Regulates 11β-Hydroxysteroid Dehydrogenase 1 Directions in Rat Leydig Cells - Zhu, Qiqi; Dong, Yaoyao; Li, Xiaoheng; Ni, Chaobo; Huang, Tongliang; Sun, Jianliang; Ge, Ren-Shan (Frontiers in Endocrinology, 2020)
Background: The purpose of this study was to investigate cytochrome P450-7B1 (CYP7B1) in the human and rat testes to regulate 11-hydroxysteroid dehydrogenase 1 (11β-HSD1) activity. We hypothesized that dehydroepiandrosterone (DHEA) and its product 7α-hydroxydehydroepiandrosterone (7OHD) after catalysis of CYP7B1 played a critical role in deriving the direction of 11-HSD1, because 7OHD is an alternative substrate for 11β-HSD1. Methods: We examined the influence of DHEA and 7OHD on 11β-HSD1 activities in both intact Leydig cells and microsomes using radioactive substrates and identified the location of CYP7B1 in Leydig cells using immunohistochemical staining and qPCR. Results: We found that DHEA stimulated 11β-HSD1 oxidase activity in intact cells (EC50 = 0.97  0.11 µM) and inhibited its reductase activity (IC50 = 1.04  0.06 µM). In microsomes, DHEA was a competitive inhibitor of the reductase activity. The 11β-HSD1 oxidase activity in intact cells was inhibited by 7OHD (IC50 = 1.18  0.12 µM), and the reductase activity was enhanced (EC50 = 0.07  0.04 µM). 7OHD was a competitive inhibitor of 11β-HSD1 oxidase. CYP7B1 was present in rat Leydig cells, as shown by immunohistochemistry and qPCR analysis. Conclusion: Our results are consistent with a conclusion that DHEA in the circulation contributes to 11β-HSD1 oxidase activity in Leydig cells mainly through the inhibition of reductase function of the enzyme, while its product 7OHD of CYP7B1 counteracts it.